2022
DOI: 10.3389/fendo.2022.1001065
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and adrenal gland: Myth or reality? A systematic review

Abstract: In recent years, vitamin D has become the protagonist in many studies. From cardiology to oncology the spotlight was on this vitamin. While in the past it was considered for its important role in phospho-calcium metabolism and skeletal disorders; today by studying it better, thousands of scenarios and facets have opened up on this vitamin which is actually a hormone in all respects. There are authoritative studies that demonstrate its activity in vitro and in vivo on: carcinogenesis, inflammation, autoimmunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Additionally, studies uncovered the widespread distribution and expression of the vitamin D receptor and its related metabolic enzymes in fat, pancreas, pituitary, and thyroid cells, indicating vitamin D's pleiotropic functions in health and diseases [3]. Previous studies have demonstrated that low 25(OH)D levels are related to infection [4,5], autoimmune diseases [6,7], and endocrine metabolic disorders such as diabetes [8], adrenal diseases [9], and polycystic ovary syndrome [10]. Recent evidence indicated a relationship between vitamin D concentrations and thyroid diseases, including autoimmune thyroid disease and thyroid cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies uncovered the widespread distribution and expression of the vitamin D receptor and its related metabolic enzymes in fat, pancreas, pituitary, and thyroid cells, indicating vitamin D's pleiotropic functions in health and diseases [3]. Previous studies have demonstrated that low 25(OH)D levels are related to infection [4,5], autoimmune diseases [6,7], and endocrine metabolic disorders such as diabetes [8], adrenal diseases [9], and polycystic ovary syndrome [10]. Recent evidence indicated a relationship between vitamin D concentrations and thyroid diseases, including autoimmune thyroid disease and thyroid cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“…Third, increasing vitamin D serum levels may improve TG and HDL in people with T2D. Vitamin D deficiency potentially impacts the functioning of beta cells and insulin resistance, consequently affecting lipoprotein metabolism and leading to elevated TG levels and decreased HDL levels (58). Lastly, vitamin D may reduce TG levels by regulating parathyroid hormone (PTH).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, vitamin D may reduce TG levels by regulating parathyroid hormone (PTH). The elevation of PTH levels may lead to an increase in the production of TG, and the presence of vitamin D inhibits the secretion of PTH in the bloodstream (58,59).…”
Section: Discussionmentioning
confidence: 99%